The Influence of Microsoft Power Point Based Video Learning Media on Social Studies Learning Outcomes of Elementary School Students: Pengaruh Media Pembelajaran Video Berbasis Microsoft Power Point Terhadap Hasil Belajar IPS Siswa Sekolah Dasar - Fauziyah, Ni'matul; Afandi, Rifki (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine whether or not there is an influence and the level of influence of using Microsoft Power Point-based video learning media on social studies learning outcomes for fourth grade students at SDN Keret Krembung. The research method used is quantitative with a pre-experimental design type one group pretest-posttest. The subjects of this study were elementary school students in the fourth grade at SDN Keret Krembung. Data collection techniques using tests. Data analysis used t test (paired) and eta squared formula. The results of this study indicate that there is a significant effect on social studies learning outcomes for fourth grade students at SDN Keret Krembung. The result is tcount = 18,131 which is compared to ttable = 1,711 for a significance level of 5%. It is known that the result of tcount is greater than ttable (18,131 > 1,711). Meanwhile, the results of the eta squared formula obtained a value of 0.93. This shows that the video learning media based on Microsoft Power Point has a major level of influence on the social studies learning outcomes of fourth grade students at SDN Keret Krembung.